ANATOMICAL VARIATIONS CAUSING LEFT RENAL VEIN COMPRESSION IN NUTCRACKER SYNDROME: A CASE REPORT (Vietnam Journal of Community Medicine, 2026)
Background: Nutcracker syndrome refers to compression of the left renal vein between the superior mesenteric artery and the abdominal aorta. Although uncommon, it is an important diagnosis because of its associated complications, including the risk of chronic kidney disease secondary to prolonged renal venous hypertension and the potential development of renal vein thrombosis.Case presentation: A 52 year old female with no significant past medical history presented with dull left flank pain and lower abdominal pain associated with severe dysmenorrhea. Computed tomography demonstrated compression of the left renal vein between the abdominal aorta and the superior mesenteric artery, along with dilatation of the ovarian vein. With a diagnosis of Nutcracker syndrome, the patient underwent ovarian vein embolization. Following the intervention, the patient experienced significant symptom relief and was discharged after 2 days. Follow-up examinations at 1 month and 3 months showed favorable outcomes.Conclusion: Ovarian vein embolization may represent a minimally invasive and effective therapeutic option for patients with Nutcracker syndrome presenting predominantly with pelvic congestion syndrome. However, treatment strategies should be individualized for each specific case.
Keywords: Nutcracker syndrome, left renal vein, pelvic congestion syndrome, ovarian vein embolization.